A Review on Energy Efficient CMOS Digital Logic - Dokic, B. L. (Engineering, Technology & Applied Science Research, 2013)
Autonomy of power supply used in portable devices directly depends on energy efficiency of digital logic. This means that digital systems, beside high processing power and very complex functionality, must also have very low power consumption. Power consumption depends on many factors: system architecture, technology, basic cells topology-speed, and accuracy of assigned tasks. In this paper, a review and comparison of CMOS topologies techniques and operating modes is given, as CMOS technology is expected to be the optimum choice in the near future. It is shown that there is a full analogy in the behavior of digital circuits in sub-threshold and strong inversion. Therefore, synthesis of digital circuits is the same for both strong and weak operating modes. Analysis of the influence of the technology, MOS transistor threshold voltage (Vt) and power supply voltage (Vdd) on digital circuit power consumption and speed for both operating modes is given. It is shown that optimal power consumption (minimum power consumption for given speed) depends on optimal choice of threshold, and power supply voltage. Multi Vdd /Vt techniques are analyzed as well. A review and analysis of alternative logical circuit’s topologies – pass logic (PL), complementary pass logic (CPL), push-pull pass logic (PPL) and adiabatic logic – is also given. As shown, adiabatic logic is the optimum choice regarding energy efficiency.